Manajemen Kesiswaan Dalam Mengembangkan Potensi Siswa Di SD Muhammadiyah - Suhasti, Asih; Suyatno, Suyatno; Santosa, Achadi Budi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
The development of students’ potential is not limited to academic aspects but also includes non-academic aspects that require systematic and sustainable student management. SD Muhammadiyah, as an educational institution that emphasizes holistic education, needs to implement effective student management to optimize students’ talents and interests. This study aims to analyse the implementation of student management in developing students’ potential at SD Muhammadiyah, covering the stages of planning, organizing, actuating, and controlling. This research employed a qualitative approach using a case study method. Data were collected through observation, interviews, and documentation involving the principal, vice principal for student affairs, classroom teachers, and extracurricular instructors. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results indicate that student management is implemented in an integrated manner through four main functions. The planning stage is based on the school’s vision and mission, supported by budgeting through the School Revenue and Expenditure Budget (RAPBS) and the implementation of initial diagnostic assessments. The organizing stage includes grouping students into categories of academically gifted, talent-gifted, and interest-based students, as well as providing adequate facilities and infrastructure. In the actuating stage, students’ potential is developed through differentiated instruction, scheduled and intensive coaching, the formation of competition teams, and active collaboration with parents. The controlling stage is carried out through regular evaluation meetings, monitoring of students’ achievements, and follow-up actions to improve programs. Overall, the implementation of systematic and sustainable student management has proven effective in supporting the optimal development of students’ potential.